The Influence of Fermentation Time in the Physical and Chemical Composition of Fermented Soybean Husk by Using Aspergillus niger on the Quality of Raw Feed Materials - Ihtifazhuddin, Muhammad Ikhwan; Nursyam, Happy; Ekawati, Arning Wilujeng (The Journal of Experimental Life Science, 2016)
Soybean husk (Glycine max L. Merrill) a soybean processing waste as raw material for tempe obtained after the process of boiling and soaking soybeans. The main problem in the use of soybean husk (Glycine max L. Merrill) as feed material is its crude fiber content which is fairly high. This study aimed to observe the fermented soybean husk using Aspergillus niger to improve the quality of the raw feed materials. This was conducted by using completely randomized design (CRD) analysis and repeated three times; the time optimization of Aspergillus niger in 2, 4, and 6 days based on chemical analyses (moisture, protein, fat, ash, crude fiber and feed containing carbohydrates (NFE) and physical assessment fermentation (smell, texture, moisture and hyphae) were analyzed descriptive qualitatively. The results showed that 4 days fermentation of soybean husk using A. niger is successful gives the highest score based on physical characteristics texture, aroma, moisture, and the formed hyphae and the most effective treatment for decrease in crude fiber is 13% and increase in NFE contained in the largest on 4 days fermented soybean husk by Aspergillus niger with a long time 4 days. Keywords: Aspergillus niger, fermentation, soybean husk.